Pengaruh Persepsi Siswa Kepada Guru Matematika Dalam Mengelola Kelas Terhadap Minat Belajar Siswa Kelas XI di SMK Negeri 1 Mataram Tahun Pelajaran 2019/2020 - Yuniarti, Ni Nyoman Dewi; Soeprianto, Harry; Kurniawan, Eka (Jurnal Ilmiah Pendidikan Indonesia, 2020)
This research aimed to determine students' perception to mathematics teacher in managing classes, mathematics learning interest, and the influence of students' perception to mathematics teacher in managing classes toward students learning interest of grade XI in SMK Negeri 1 Mataram academic year 2019/2020. This research used quantitative approach with descriptive type. The subjects in this research were students of grade XI in SMK Negeri 1 Mataram academic year 2019/2020, namely students of grade XI (Perkantoran, Kecantikan, Akuntansi 1, Akuntansi 2, Tata Busana, Perhotelan, and Multimedia). Data were collected using a questionnaire instrument and using interview guidelines. From the results of this research, it could be seen that students' perception to mathematics teacher in managing classes were included in good criteria. Meanwhile for mathematics learning interest included in moderate criteria. From the calculation results t-test was obtained = 10.788 > = 1.97 and it could be concluded that there was an influence students' perception to mathematics teacher in managing classes toward students learning interest of grade XI in SMK Negeri 1 Mataram academic year 2019/2020 with a contribution of 35.7%.